THE FIRST RECORD OF NEMKOVELIA DAGUINI (NEUMANN, 1958) FROM THE MIDDLE-UPPER EOCENE OF OMAN (ARABIAN PENINSULA) AND MEGHALAYA (INDIAN SUBCONTINENT) AND ITS SIGNIFICANCE IN TETHYAN CORRELATIONS AND PALEOBIOGEOGRAPHY - Ozcan, Ercan; Erbay, Sadikcan, I; Abbasi, Iftikhar Ahmed; Pereira, Christer Dominique; Erkizan, Levent Sina; Kaygili, Sibel (Univ Studi Milano, 2019)
Nemkovella daguini (Neumann, 1958) is a small-sized orthophragminid species previously reported from the Lutetian to lower Priabonian shelf deposits of the peri-Mediterranean region (Western Tethys). This species, originally established from the Aquitaine Basin (France), differs significantly from typical nemkovellas and other orthophragminids by having isolated adauxiliary and orbitoidal chamberlets that progressively give rise to the formation of typical annular chambers in the neanic stage. We record here for the first time this species from the lower Priabonian Tahwah Formation in the Arabian Peninsula and from the transitional middle-upper Eocene Prang Formation in Meghalaya (India), giving a detailed description and biotnet ry. This expands the geographic range of N. daguini to the Eastern Tethys, allowing us to provide an enhanced scheme for the correlation of peri-Mediterranean deposits with those from the South Asia. In previous studies the majority of the larger benthic foraminiferal (LBF) fauna from this region were considered to belong to the Indo-Pacific bioprovince. The LBF in Tahwah Formation, on the other hand, are here considered to have greater affinity with those of Western Tethys based on the occurrence of Heterostegina reticulata,Nummulites bormoensis, Assilina gr. sckvageti-alpina, and Silvestriella tetraedra. The occurrence of Pellatispira in this unit, represented by at least two species, shows Indo-Pacific influence in Oman.
Keywords: Nemkovella daguini; systematics; paleobiogeography; Eocene; Oman; India